Effective dose evaluation of NORM-added consumer products using Monte Carlo simulations and the ICRP computational human phantoms. (April 2016) - Lee, Hyun Cheol; Yoo, Do Hyeon; Testa, Mauro; Shin, Wook-Geun; Choi, Hyun Joon; Ha, Wi-Ho; Yoo, Jaeryong; Yoon, Seokwon; Min, Chul Hee
Abstract: The aim of this study is to evaluate the potential hazard of naturally occurring radioactive material (NORM) added consumer products. Using the Monte Carlo method, the radioactive products were simulated with ICRP reference phantom and the organ doses were calculated with the usage scenario. Finally, the annual effective doses were evaluated as lower than the public dose limit of 1 mSv y −1 for 44 products. It was demonstrated that NORM-added consumer products could be quantitatively assessed for the safety regulation. Abstract : Highlights: Consumer products considered that NORM would be included should be regulated. 44 products were collected and its gamma activities were measured with HPGe detector. Through Monte Carlo simulation, organ equivalent doses and effective doses on human phantom were calculated. All annual effective doses for the products were evaluated as lower than dose limit for the public.